Petro-physical analysis of well logs for reservoir evaluation: a case study of Well 1 and 2 of the ‘Ictorian’ field in the Niger Delta Basin - G.E. Maju-Oyovwikowhe; V.K. Njoku (Journal of Applied Sciences and Environmental Management, 2019)
This study presents the log analysis results of a suite of conventional wireline logs including gamma ray, density, neutron, and resistivity from two wells in ‘Ictorian’ Field located in the Niger delta with the aim of evaluating hydrocarbon prospect of the field. Results obtained showed presence of hydrocarbon in eleven (11) reservoirs from well 1, and four (4) reservoirs from well 2. Well 1 and 2 both had hydrocarbon reservoir bearing gas. Well 1 had Gas Water contact at 2497m and 2964m, while well 2 had Gas water Contacts at 1739m and 2510m. Effective porosities had values ranging from 26-16% in well 1. In well 2, effective porosities had values ranging from 22-17%.The values obtained show that the analysed reservoirs have good permeability. The calculated values indicate that porosity, permeability values from the hydrocarbon bearing reservoirs are good enough for commercial accumulation in the Niger Delta. It is recommended that for field optimization mud logging data and core data analysis should be integrated as part of the evaluation exercise.